The Influence Of Competence, Work Motivation, And Leadership On Teacher Performance At SMA Negeri 4 Seluma - Angga, Angga; Indriasari , Nia; Putra , Iswidana Utama (Universitas Dehasen Bengkulu, 2025)
The performance of human resources in educational institutions is one of the keys to the success of the educational process. Therefore, schools need to prepare human resources who are qualified and competent in their fields, and efforts are needed to improve the quality of human resources in educational institutions. The purpose of this research is to determine the influence of Competence, Work Motivation, and Leadership on Teacher Performance at SMA Negeri 4 Seluma. The analysis methods used in this study include Validity Test, Reliability Test, Multiple Linear Regression Analysis, Coefficient of Determination, and Hypothesis Testing using t-test and F-test with a sample of 47 respondents. From the calculations using SPSS, we can see that competence and work motivation affect but are not significant to teacher performance. Leadership, on the other hand, affects and is significant to teacher performance. From the SPSS calculations, it is known that the determination coefficient value of the variables competence, work motivation, and leadership is 0.791, which can be understood that the X variables have a positive effect on teacher performance (Y) at SMA Negeri 4 Seluma, amounting to 79.1%, while the remaining 20.9% is influenced by variables that were not studied.